Effects of industrial effluent on wetland macroinvertebrate community structures near a wastewater treatment facility - Meaghan E. Quanz (Elsevier, 2021)
Macroinvertebrate communities and environmental variables were examined in wetlands near an industrial wastewater treatment facility to assess impacts from exposure to historical effluents. Baseline wetland assessments were required prior to cleanup of contaminated sediments at the facility. The study included wetlands historically exposed to direct effluent discharge, wetlands exposed to current effluent discharge (at the time of sampling), and reference wetlands. Wetlands were sampled in June, July, and September 2018 using a new macroinvertebrate community monitoring protocol (“Wetland CABIN”) developed by Environment and Climate Change Canada. Macroinvertebrates were counted and identified to Family level. Data were qualitatively analyzed using pie charts and nonmetric multidimensional scaling, as well as quantitatively with the Shannon-Weiner diversity index, the Berger-Parker index and using pollution sensitivity values. Correlations using Spearman rho were also calculated between indices and measured environmental variables. Wetlands near the treatment facility were not significantly different compared to reference sites. Macroinvertebrate communities near the treatment facility appeared to be relatively unimpacted by historical effluent inputs. The Wetland CABIN protocol may be a useful monitoring tool for assessing wetland macroinvertebrate community structure because it allows for standardized approaches to be used to compare temporal changes at contaminated sites or spatially between sites.